African Peace and Security Architecture (APSA) - (:unkn) unknown (My University, 2022)
At the 2002 Durban conference, the birth of the African Union, which had taken over from the Organisation of African Unity, was marked by the intention of African leaders to solve by themselves security issues on their continent. It gave birth to a collective security system: the African Peace and Security Architecture (APSA). Unfortunately, the APSA does not work. The first section of this chapter is an assessment which leads to conclude that APSA has become a budgetary chasm in which international donors, mainly the European Union, finance a security technocraty based in Addis Abeba, which sole outcome is organising unproductive meetings and reacting too late while the situation on the ground is out of control. Second, the chapter deals systemic obstacles impeding the APSA’s operationality. Most significant among them is that APSA was originally designed on the mix of the United Nations’ Peacekeeping system and of the European Union’s Common Security and Defense Policy. The result is disconnected with the specific needs of a continent. The chapter concludes that peace and security are long-term objectives and are requiring the intensification of UNO’s direct commitment in the management of peacekeeping, and above all a strengthening of African states as providers of public services.
Keywords: African Research